Chemical mitigation of microbial pathogens in animal feed and ingredients - Cochrane, Roger Andrew (Kansas State University, 2015)
Feed mill biosecurity is a growing concern for the feed industries, especially since the entry of Porcine Epidemic Diarrhea Virus (PEDV) to the United States. Porcine Epidemic Diarrhea Virus (PEDV) is primarily transmitted by fecal-oral contamination. However, research has confirmed swine feed and ingredients as potential vectors of transmission, so strategies are needed to mitigate PEDV in feed. The objective of the first experiment was to evaluate the effectiveness of various chemical additives to prevent or mitigate PEDV in swine feed and ingredients that had been contaminated post-processing. Time, formaldehyde, medium chain fatty acids, essential oils, and organic acids all enhance the degradation of PEDV RNA in swine feed and ingredients, but their effectiveness varies within matrix. Notably, the medium chain fatty acids were equally as successful at mitigating PEDV as a commercially-available formaldehyde product. Salmonella is also another potential feed safety hazard in animal feed ingredients. Thermal mitigation of Salmonella in ingredients and feed manufacturing is effective, but it does not eliminate the potential for cross contamination. Therefore, the objective of the second experiment was to evaluate the effectiveness of chemicals to mitigate Salmonella cross-contamination in rendered proteins over time. Both chemical treatment and time reduced Salmonella concentrations, but their effectiveness was again matrix dependent. Chemical treatment with medium chain fatty acids or a commercial formaldehyde product was most effective at mitigating Salmonella in rendered protein meals. The final experiment was conducted to evaluate the effectiveness of a dry granular acid, sodium bisulfate (SBS; Jones-Hamilton, Co., Waldridge, OH), to mitigate contamination of Salmonella in poultry feed. A surrogate organism, Enterococcus faecium, was utilized for this research in order to evaluate the effectiveness of SBS. Thermal processing, SBS concentration, and time all impacted biological pathogen levels in poultry diets, and including a dry granular acid may be an effective method to reduce pathogen risk. However, the most significant reduction of Enterococcus faecium was due to thermal mitigation. Notably, pelleting reduced Enterococcus faecium by 2-3 logs on day 0. In summary, both thermal processing and chemical inclusion can be used to reduce the risk of microbial pathogens in feed.
Keywords: PEDV; Salmonella; Feed safety; Biosecurity; Chemical treatment; Mitigation; Agriculture, General (0473); Animal Diseases (0476); Animal Sciences (0475)